Formative Investigation of the Links Between Gambling (Including Problem Gambling) and Crime in New Zealand - Bellringer, M; Abbott, Max; Coombes, R; Brown, R; McKenna, B; Dyall, L; Rossen, F (Auckland University of Technology (AUT), 2009)
Crime (illegal behaviours) constitutes a continuum ranging from undetected, unreported, and unprosecuted crimes through to prosecuted, convicted and sentenced crimes; any of these may be associated with gambling/problem gambling. There may also be behaviours considered marginally illegal, for example welfare beneficiaries obtaining additional benefit and not disclosing that benefit money has been used for gambling, or business owners using business cash for gambling and not declaring cash as income for tax purposes. These behaviours are difficult to detect and even if detected may be considered morally socially unacceptable but not necessarily criminal and thus not reported to police. There may also be other behaviours, for example embezzlement of employer funds or stealing from family that are clearly criminal and may be detected, but are not likely to be reported to save embarrassment of either the victim or the perpetrator, or even to protect the perpetrator. In some instances, these crimes are not readily linked to gambling. Additionally, there are financial crimes to support gambling, situational crimes associated with gambling venues, violence associated with gambling and family/whanau crime associated with gambling. In November 2006, the Gambling and Addictions Research Centre at Auckland University of Technology, in collaboration with the Centre for Gambling Studies at the University of Auckland, was commissioned by the Ministry of Health to conduct the research project Problem gambling – Formative investigation of the links between gambling (including problem gambling) and crime in New Zealand. The purpose of this project was to develop a better understanding of the nature of the links between gambling and crime, with particular reference to unreported crime and the nature of the resulting harms experienced by individuals, families/whanau and communities.